Knitted strain sensor with carbon fiber and aluminum-coated yarn, for wearable electronics. Issue 46 (10th November 2021) - Jang, Junhyeok; Kim, Suji; Lee, Kangmin; Park, Seungjun; Park, Geum-Yong; Kim, Byoung-Joon; Oh, Junghun; Lee, Mi Jung
Abstract : A knitted textile-type strain sensor with RRAM characteristics is developed. We demonstrated that the developed sensor has a higher sensitivity than previously demonstrated textile strain sensors and can be used as a motion sensor by applying it to clothes. Abstract : A knitted textile-type strain sensor with resistive random access memory (RRAM) characteristics is developed. This study focuses on the change in resistance at the contact between carbon and aluminum fibers along the strain to develop a strain sensor that can be used in smart clothing. Unlike conventional textile sensors that use only one type of conducting yarn, this study proposes a new configuration that uses two different materials to obtain a large change in resistance value. The all-in-one yarn, comprising carbon fibers, aluminum-coated yarns, and normal yarns, was used to construct sensor devices by knitting. In this knitted textile, the resistance switching characteristics of the RRAM between aluminum and carbon were observed as confirmed in previous studies for flat devices and woven textiles. Along the strain applied to the knitted fabric sensor, the change in the resistance along the stretching was detected and verified through a physical mechanism of the change in the contact area. The sensitivity of the developed knitted strain sensor is more than 10 times higher than previously demonstrated textile strain sensors. Also, cyclic testing of the sensor between the stretched and the recovered state on a machine and on a knee was demonstrated to prove that it can be used as a motion sensor by applying it to the joint part of clothing. In addition, there are advantages of low-cost and large-scale production that are possible since this yarn can be used in existing fabric production industries.